Efek Persuasi Peribahasa Serta Implementasi Pembelajarannya di SMA - Panji Setyo Wiguno (Universitas Tidar, 2017)
This research background on learning basic competencies 12.2 proverbs in writing the idea to convince or persuade the reader to be or do something in paragraph form of persuasion. Lessons are included in the curriculum for the class x KTSP second semester. The problems of this study (1) what are the effects of persuasion contained in proverbs, (2) how the implementation of learning persuasion School (SMA), based on a review pragmatic in proverbs. Based on the formulation of the problem this study aims to (1) describe the effect of persuasion proverbs, (2) make a persuasive learning design maxim in high school. This study uses several theories as follows: (1) pragmatics, (2) aspects of meaning, (3) the meaning of persuasion, (4) proverb. The data source of this research was obtained from the Dictionary of Proverbs J.S Badudu and Kamusperibahasa.com (attached data). Collecting data in this study using methods refer to proceed with the log. Data analysis using a unified and pragmatic pilah power. This study is structured to be a design study in high school. X classes the second semester, the curriculum KTSP. 12.2 Basic competencies writing ideas to convince or persuade the reader to be or do something in paragraph form of persuasion. Based on the results of 11 Data maxim that has been investigated is found maxim that has been referred to the effects of persuasion effect of ethical 1 data, the sensitizing effect 1 data, the effect humble 2 data, the effect of wisdom 2 data, the effect of fidelity 2 data, the effect of simplicity 1 record, effects alertness 1 data, the effect unyielding 1 data. This study used high school level instructional design, object of this study in accordance with the learning materials at high school based curriculum KTSP.Keywords: review pragmatic, persuasion effects category, proverbs.